Glucagon-Like Peptide-1 Receptor Agonist Liraglutide Ameliorates the Development of Periodontitis - Noritaka Sawada; Kei Adachi; Nobuhisa Nakamura; Megumi Miyabe; Mizuho Ito; Shuichiro Kobayashi; Shin-ichi Miyajima; Yuki Suzuki; Takeshi Kikuchi; Makoto Mizutani; Taku Toriumi; Masaki Honda; et al. (Journal of Diabetes Research)
Periodontitis is one of the diabetic complications due to its high morbidity and severity in patients with diabetes. The prevention of periodontitis is especially important in diabetic patients because the relationship between diabetes and periodontitis is bidirectional. Here, we evaluated the impacts of glucagon-like peptide-1 (GLP-1) receptor agonist liraglutide on the amelioration of periodontitis. Five-wk-old Male Sprague–Dawley (SD) rats (n=30) were divided into 3 groups: normal, periodontitis, and periodontitis with liraglutide treatment groups. Periodontitis was induced by ligature around the maxillary second molar in SD rats. Half of the rats were administered liraglutide for 2 weeks. Periodontitis was evaluated by histological staining, gene expressions of inflammatory cytokines in gingiva, and microcomputed tomography. Periodontitis increased inflammatory cell infiltration, macrophage accumulation, and gene expressions of tumor necrosis factor-α and inducible nitric oxide synthase in the gingiva, all of which were ameliorated by liraglutide. Liraglutide decreased M1 macrophages but did not affect M2 macrophages in periodontitis. Moreover, ligature-induced alveolar bone resorption was ameliorated by liraglutide. Liraglutide treatment also reduced osteoclasts on the alveolar bone surface. These results highlight the beyond glucose-lowering effects of liraglutide on the treatment of periodontitis.